A Paleopolar Dinosaur Track Site in the Cretaceous (Maastrichtian) Prince Creek Formation of Arctic Alaska: Track Characteristics and Probable Trackmakers. Issue 2 (3rd July 2018) - Flaig, Peter P.; Hasiotis, Stephen T.; Fiorillo, Anthony R.
ABSTRACT: For the first time a dinosaur track site is identified in Maastrichtian paleopolar coastal plain deposits of the Prince Creek Formation (PCF) along the Colville River, North Slope of Alaska. Tracks were made and preserved by trampling of an ash-covered swamp margin, subsequent filling of tracks with alluvium from nearby rivers, and modification of sediments by pedogensis. Tracks are grouped into three classes based on track width and depth, with the largest tracks (>800 mm wide) recording overstepping by multiple individuals. As no bedding plane views of the tracks are present, the true shapes of the tracks were not available and, thus, a high probability of identification is not achievable. The tracks can be interpreted, however, using hypothetical-deductive reasoning by integrating paleontological and ichnological data from local and regional outcrops. The tracks likely represent the presence of hadrosaurs based on the overwhelming percentage of hadrosaur fossils that comprise nearby bonebeds, dominated by juvenile hadrosaurs (∼ 99%); to date no adult hadrosaur bone has been documented in the PCF. This interpretation is also supported by comparison of PCF hadrosaur track dimensions to exquisitely preserved (three-dimensional tracks with skin impressions) trackways of the coeval Cantwell Formation in Denali National Park (DENA), central Alaska. PCF track size dimensions, in comparison to DENA tracks, also represent a series of growth stages including both juvenile and adult hadrosaurs, and indicate that multiple generations and sizes of individuals lived and traveled together on the Arctic Alaska coastal plain. This is the first evidence for adult hadrosaurs in the PCF. This track site also preserves the highest latitude Maastrichtian footprints known.